Vibration-proof rubber composition and vibration-proof rubber
By using a specific proportion of natural rubber, isopropylene rubber and butadiene rubber in anti-vibration rubber, and adding specific anti-aging agents and vulcanizing agents, the lack of thermal stability and thermal shrinkage resistance of anti-vibration rubber in the prior art is solved, and the balance of low dynamic magnification and high thermal stability is achieved.
Patent Information
- Application Number
- JP2023145715
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-08
AI Technical Summary
The prior art is difficult to achieve high thermal stability and heat shrink resistance of vibration-resistant rubber while maintaining low dynamic amplification.
A rubber composition comprising natural rubber (NR), isopropylene rubber (IR) and butadiene rubber (BR) as the main rubber components is used, and a composition containing 2-mercaptobenzolazine zinc salt, N,N'-di-navl-p-phenylenediamine and sulfur as the vulcanizing agent, and a specific amount of tetraethylthiocyanamide disulfate as the vulcanizing agent.
It realizes that while maintaining low dynamic amplification, the thermal stability and heat shrink resistance of anti-vibration rubber are improved, and its long-term thermal stability performance is enhanced.
Smart Images

Figure 2025039000000011 
Figure 2025039000000001 
Figure 2025039000000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-vibration rubber composition that is used in anti-vibration rubber such as bushes for vehicles such as automobiles, and that has excellent vibration-isolating properties against vibration as well as excellent heat resistance (heat aging resistance), heat setting resistance, etc., and to an anti-vibration rubber that uses the anti-vibration rubber composition and has excellent heat-resistant adhesion. [Background technology]
[0002] Conventionally, in various vehicles such as automobiles, for example, in order to improve passenger comfort, various types of vibration-isolating rubber have been placed in areas that are the source of vibration to block and suppress the transmission of vibration, thereby reducing the intrusion of vibration and noise into the vehicle interior and reducing the diffusion of noise into the surrounding environment.
[0003] It is known that reducing the dynamic spring constant (Kd) is effective in improving the vibration isolation properties of anti-vibration rubber, i.e., blocking the transmission of vibration. However, since anti-vibration rubber is required to withstand a certain static force, such as when supporting a heavy object, the static spring characteristic (Ks) must be relatively large. Therefore, it is desirable for the value of the dynamic magnification (=Kd / Ks), which is the ratio of the dynamic spring constant (Kd) to the static spring constant (Ks), to be small (i.e., a low dynamic magnification). Furthermore, it is desirable for anti-vibration rubber to have desired material properties, such as high durability against deformation due to repeated vibration.
[0004] In order to meet such required performance (low dynamic magnification and high durability), diene-based blend rubber (hereinafter simply referred to as diene-based rubber) made by blending natural rubber (NR) and / or isoprene rubber (IR) with butadiene rubber (BR) is often used as the rubber component in anti-vibration rubber for vehicles. In addition, anti-vibration rubber is also required to have, for example, heat resistance (heat aging resistance), heat setting resistance, etc., so that it can withstand use in harsh thermal environments and heat from heat sources. However, diene rubbers made of natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) are known to have poor heat resistance.
[0005] In response to this problem, various proposals have been made regarding various antioxidants and vulcanization systems (vulcanization accelerators and vulcanization agents) in order to improve the heat resistance of the diene rubber. For example, a diene rubber composition (Patent Document 1) has been proposed in which the blending ratio of the antioxidant is set so that the blending amount of the amine-based antioxidant is set within the range of 0.5 to 3 moles per mole of the benzimidazole group of the benzimidazole-based antioxidant, and the total blending amount of the antioxidant is set within the range of 1 to 10 parts by weight per 100 parts by weight of the rubber component. In addition, a vibration-proof rubber composition (Patent Document 2) in which natural rubber containing a specified amount of 2-mercaptobenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and butadiene rubber are blended, and a vibration-proof rubber composition (Patent Document 3) containing a compound having a carbon-carbon double bond at the terminal and a carbonyl group at the α-position, and an imidazole-based antioxidant, etc. have also been proposed.
[0006] As for vulcanization systems (vulcanization accelerators and vulcanizing agents), a technology is known in which crosslinking (vulcanization) is carried out using sulfur donor compounds (sulfur donors) such as tetramethylthiuram disulfide (TMTD) or 4,4'-dithiodimorpholine, which contain a small amount of sulfur or no sulfur, thereby improving heat resistance. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2002-194140 A [Patent Document 2] Japanese Patent Application Publication No. 11-116733 [Patent Document 3] JP 2015-025060 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described in the above proposal, it is well known that butadiene rubber is contained in the rubber component to obtain desired vibration-damping properties (low dynamic magnification, etc.). However, when an antioxidant is contained, the dynamic magnification often increases, and depending on the type and amount of the antioxidant used, it may be difficult to achieve both vibration-damping properties and heat resistance and heat setting resistance as desired.
[0009] For example, Patent Document 1 describes the use of a rubber component containing a terminal-modified butadiene rubber, an imidazole-based antioxidant, and N,N'-di-β-naphthyl-p-phenylenediamine as an amine-based antioxidant in order to achieve both heat resistance and low dynamic magnification. It also describes that the blending ratio of the antioxidant is set to a range of 0.5 to 3 moles of the amine-based antioxidant per mole of the benzimidazole group of the benzimidazole-based antioxidant.
[0010] Here, 2-mercaptobenzimidazole zinc salt is represented by the following formula:
[0011] [ka]
[0012] It is a compound represented by the formula: It has two imidazole groups per molecule and a molecular weight of 397.85.
[0013] N,N'-di-β-naphthyl-p-phenylenediamine has the following formula:
[0014] [ka]
[0015] It is a compound having a molecular weight of 360.45.
[0016] In the case of Patent Document 1, since 0.5 to 3 moles of an amine-based antiaging agent are blended per mole of benzimidazole group of the benzimidazole-based antiaging agent, the blending amount of N,N'-di-β-naphthyl-p-phenylenediamine per part by mass of 2-mercaptobenzimidazole zinc salt (2 moles of imidazole group) is within the range of [0.5×360.45 / (397.85 / 2)=]0.906 parts by mass to [3×360.45 / (397.85 / 2)=]5.436 parts by mass. In other words, 2-mercaptobenzimidazole zinc salt (2 moles of imidazole group) is blended within the range of 0.184 parts by mass to 1.104 parts by mass for 1 part by mass of N,N'-di-β-naphthyl-p-phenylenediamine.
[0017] However, after detailed investigations, the present inventors found that N,N'-di-β-naphthyl-p-phenylenediamine can increase the dynamic magnification when contained in a certain amount or more in an anti-vibration rubber composition, and further improvement may be required to achieve both heat resistance and anti-vibration properties (dynamic magnification). Patent Document 1 does not disclose or even suggest anything about the effect of improving heat resistance when the content of N,N'-di-β-naphthyl-p-phenylenediamine is set relatively small (for example, set to 1 part by mass or less) and the content of 2-mercaptobenzimidazole zinc salt is set relatively high (for example, set to 1 part by mass or more).
[0018] Patent Document 2 describes a rubber that contains butadiene rubber with a cis-1,4 bond content of 97% or more in order to reduce dynamic magnification and improve resistance to sagging, and contains 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and a zinc salt of 2-mercaptobenzimidazole, or a methylated derivative thereof, as an antioxidant to improve heat resistance.
[0019] However, after detailed investigation, the inventors found that when 4,4'-bis(α,α-dimethylbenzyl)diphenylamine is contained in a certain amount or more in the vibration-proof rubber composition, it increases the dynamic magnification, and depending on the respective contents, the long-term heat resistance may be insufficient.
[0020] Patent Document 3 describes an anti-vibration rubber composition in which a compound having a carbonyl group at the α-position of a diene rubber and an imidazole-based antioxidant are added.
[0021] However, the inventors have found that, although a compound having a carbonyl group at the α-position can contribute greatly to damping properties as described in Patent Document 3, its addition to an anti-vibration rubber composition may increase the vulcanization rate and significantly decrease the scorch stability (shorten the scorch time). In addition, the anti-vibration rubber composition may scorch (premature vulcanization) during storage, or the vulcanization may progress during injection during injection molding, making molding difficult. Furthermore, although a compound having a carbonyl group at the α-position can contribute greatly to improving damping properties as described in Patent Document 3, the dynamic magnification may increase significantly, resulting in insufficient low dynamic magnification properties.
[0022] The present invention has been made in view of the above circumstances, and has an object to provide a technique that can contribute to easily achieving both vibration-proofing properties and heat resistance and heat setting resistance at the same time as desired. [Means for solving the problem]
[0023] The present inventors have conducted extensive research to obtain a vibration-proof rubber composition that achieves the above object.
[0024] As a result, the inventors discovered that in an anti-vibration rubber composition having natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) as the main rubber components, which have low dynamic magnification and excellent durability, and which contains 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur as a vulcanizing agent, and a specified amount of a specific sulfur donor compound, when the total rubber components are taken as 100 parts by mass, it is possible to obtain an anti-vibration rubber composition and anti-vibration rubber which achieve the above-mentioned objectives, and thus completed the invention.
[0025] That is, one embodiment of the anti-vibration rubber composition and anti-vibration rubber of the present invention includes the following [1] to [4].
[0026] [1] An anti-vibration rubber composition whose main rubber components are natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR), characterized in that, when the total rubber components are taken as 100 parts by mass, the anti-vibration rubber composition contains 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur, and 2 to 7 parts by mass of tetrakis(2-ethylhexyl)thiuram disulfide.
[0027] [2] A vibration-proof rubber composition whose main rubber components are natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR), characterized in that, when the total rubber components are taken as 100 parts by mass, the composition contains 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur, and 1 to 3 parts by mass of 2-(4-morpholinodithio)benzothiazole.
[0028] [3] The above [1] or [2] is a blend rubber of natural rubber (NR) and butadiene rubber (BR), the main rubber component being a ratio of natural rubber (NR) to butadiene rubber (BR) of 90 / 10 to 60 / 40 in terms of NR / BR ratio, and the butadiene rubber has a Mooney viscosity (ML 1+4 ) is preferably 50 to 75.
[0029] [4] An anti-vibration rubber, characterized in that the anti-vibration rubber composition according to any one of [1] to [3] above is vulcanization-adhered to a surface of the metal fitting via an adhesive layer provided on the surface of the metal fitting, so that the metal fitting and a vulcanized rubber made of the anti-vibration rubber composition are integrally formed. Effect of the Invention
[0030] The present invention can contribute to easily achieving both vibration-proofing properties and heat resistance and heat setting resistance at the same time as desired. [Brief description of the drawings]
[0031] [Figure 1] FIG. 1 is a schematic explanatory diagram of a test piece 1 formed using each of the anti-vibration rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Matters relating to the implementation of the present invention will be described in detail below.
[0033] As described above, the anti-vibration rubber composition of the present invention is a vibration-proof rubber composition whose main rubber components are natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR), and when the total rubber components are taken as 100 parts by mass, it contains 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 part by mass of sulfur as a vulcanizing agent, and 2 to 7 parts by mass of tetrakis(2-ethylhexyl)thiuram disulfide as a sulfur donor compound.
[0034] According to this configuration, it is possible to provide an anti-vibration rubber composition for producing an anti-vibration rubber having the desired heat resistance (thermal aging resistance), heat setting resistance, etc., while suppressing an increase in dynamic magnification.
[0035] Furthermore, instead of containing tetrakis(2-ethylhexyl)thiuram disulfide as the sulfur donor compound, 2-(4-morpholinodithio)benzothiazole may be contained (1 to 3 parts by mass). This makes it possible to provide an anti-vibration rubber composition for producing an anti-vibration rubber that has the desired heat resistance, heat setting resistance, etc., while suppressing an increase in dynamic magnification, and further has little change in vibration characteristics (spring constant) even when exposed to a heat environment for a long period of time.
[0036] In addition, the anti-vibration rubber composition may be vulcanization-adhered to the surface of the metal fitting via an adhesive layer provided on the surface of the metal fitting, thereby making it possible to provide an anti-vibration rubber having excellent heat-resistant adhesion in which the metal fitting and vulcanized rubber made from the anti-vibration rubber composition are integrally formed.
[0037] Next, each component applicable to the anti-vibration rubber composition and anti-vibration rubber (rubber molded product) of this embodiment will be described. Note that, hereinafter, when indicating the content of all components (materials), it may be simply written as parts by mass, but it means the parts by mass of the components when the total rubber components are 100 parts by mass.
[0038] [Rubber component] In the anti-vibration rubber composition according to the present embodiment, natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) are used as the main rubber components in the rubber component. This main rubber component means that the total amount of natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) is 90 mass % or more of the total rubber component.
[0039] The rubber component preferably contains natural rubber from the viewpoint of, for example, the stability of rubber strength and the durability of the anti-vibration rubber. There are no particular limitations on the natural rubber, and for example, normal natural rubber used in anti-vibration rubber can be used. Specifically, for example, sheet rubber (including crepe) includes all grades of RSS (RIBBED SMOKED SHEET), WHITE CREPES, PALE CREPES, ESTATE BROWN CREPES, COMP CREPES, THIN BROWN CRAPES (RIMILLS), THICH BLANCKET CRAPES (AMBERS), FLAT BARK CREPES, and PURE SMOKED BLANKET CRAPES, and for block rubber, include SMR (STANDARD MALAYSIAN RUBBER), SIR (STANDARD INDONESIAN RUBBER), STR (STANDARD THAI RUBBER), SSR (STANDARD SINGAPOREAN RUBBER), SCR (STANDARD CEYLON RUBBER), and SVR (STANDARD VIETNAMESE RUBBER).
[0040] In addition, the rubber component preferably contains butadiene rubber (BR) from the viewpoint of low dynamic magnification and durability. That is, it is preferable that the rubber is a diene rubber blended with natural rubber (NR) and butadiene rubber (BR). The compounding ratio of natural rubber (NR) and butadiene rubber (BR) can be appropriately set, and an example thereof is a natural rubber (NR) / butadiene rubber (BR) ratio in the range of 90 / 10 to 50 / 50 (mass ratio), preferably in the range of 90 / 10 to 60 / 40. In the case of such a range, it is possible to obtain an anti-vibration rubber having excellent durability and low dynamic magnification. In the natural rubber (NR) / butadiene rubber (BR), as the ratio of natural rubber (NR) increases, the vulcanized rubber strength is excellent in stability with a high value, and the durability variation is reduced. On the other hand, as the ratio of butadiene rubber (BR) increases, it becomes easier to obtain an anti-vibration rubber composition having excellent low dynamic magnification.
[0041] The butadiene rubber (BR) applicable to this embodiment is not particularly limited, and for example, a normal butadiene rubber used in anti-vibration rubber can be used. When emphasis is placed on durability against repeated deformation, the higher the cis 1,4-bond content, the better, and as an example, a butadiene rubber (high cis BR) having a cis 1,4-bond content of 90% or more is preferred, and a high cis BR having a cis 1,4-bond content of 93% or more is more preferred.
[0042] In addition, for butadiene rubber (BR) with the same chemical composition, the Mooney viscosity (ML 1+4 The higher the Mooney viscosity (ML) at 100°C, the higher the molecular weight and the better the durability. 1+4 It is preferable to use a material having a Mooney viscosity (ML 1+4 ) increases, the flowability of rubber tends to decrease, and the Mooney viscosity (ML 1+4 If the Mooney viscosity (ML) at 100° C. is too high, the kneading processability and molding processability of the rubber material composition may be easily deteriorated. 1+4 It is preferable to use a material having a Mooney viscosity (ML 1+4 ) should be 65 or less.
[0043] Specific examples of such butadiene rubbers include BR730, BR54, BR740 (all manufactured by ENEOS Materials), Ubepol 390L (manufactured by Ube Industries), BUNA CB21, CB22, CB1221 (all manufactured by ARLANXEO), etc. On the other hand, when a lower dynamic magnification is more required, for example, a terminal-modified butadiene rubber whose terminals have been modified with N-methylpyrrolidone groups (for example, Nipol 1250H manufactured by Nippon Zeon Co., Ltd.) can be preferably used.
[0044] Isoprene rubber (IR) exhibits similar performance to natural rubber (NR), contains fewer impurities such as foreign matter, and can often be used as a substitute for natural rubber (NR). On the other hand, in terms of the stability of rubber strength and durability, natural rubber (NR) often gives better results, making it preferable to use it.
[0045] In addition, for the purpose of improving processability, etc., there is no problem if a rubber component other than diene rubber such as styrene butadiene rubber (SBR) or EPDM is appropriately contained (for example, a small amount within the range of 10 parts by mass or less).
[0046] [Anti-aging agent] The anti-vibration rubber composition used in the rubber molded article of this embodiment contains, as essential components, 2-mercaptobenzimidazole zinc salt and N,N'-di-2-naphthyl-p-phenylenediamine as antioxidants.
[0047] 2-Mercaptobenzimidazole zinc salt is known as a secondary antioxidant, and is often used in combination with various amine-based or phenol-based antioxidants, which are primary antioxidants, generally at 1 part by mass or less.
[0048] On the other hand, in this embodiment, the 2-mercaptobenzimidazole zinc salt is contained within the range of 1.8 parts by mass to 5 parts by mass. If the content of this 2-mercaptobenzimidazole zinc salt is less than 1.8 parts by mass, the effect of improving heat resistance over a long period of time may not be sufficiently obtained. On the other hand, if the content of the 2-mercaptobenzimidazole zinc salt is more than 5 parts by mass, the effect of further improving heat resistance is not obtained, and the compression set resistance tends to become large. A more suitable content of the 2-mercaptobenzimidazole zinc salt is in the range of 1.9 parts by mass to 4 parts by mass.
[0049] As a similar antiaging agent, 2-mercaptobenzimidazole-based antiaging agents are known, such as 2-mercaptobenzimidazole and 2-mercaptomethylbenzimidazole. However, in a vibration-proof rubber composition containing natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) as the main rubber component, containing 0.2 to 0.7 parts by mass of sulfur as a vulcanizing agent, and containing a vulcanization accelerator that serves as a sulfur donor, as in the present embodiment, the 2-mercaptobenzimidazole has a smaller effect of improving long-term heat resistance than the 2-mercaptobenzimidazole zinc salt, and may increase the compression set resistance rate. In addition, the 2-mercaptomethylbenzimidazole may have a large improvement effect in terms of heat resistance, similar to the 2-mercaptobenzimidazole zinc salt, but it tends to increase the compression set resistance rate, and is not suitable for vibration-proof rubber.
[0050] The vibration-proof rubber composition used in the rubber molded product of this embodiment contains 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine as an amine-based antiaging agent. This N,N'-di-2-naphthyl-p-phenylenediamine is known to have low volatility due to heating and to remain in the vulcanized rubber for a long period of time, and is suitable for use from the viewpoint of long-term heat resistance. In addition, when the N,N'-di-2-naphthyl-p-phenylenediamine is used in combination with 2-mercaptobenzimidazole zinc salt, the combined effect may provide a sufficient improvement in long-term heat resistance even if the content of the N,N'-di-2-naphthyl-p-phenylenediamine is small.
[0051] On the other hand, if the content of the N,N'-di-2-naphthyl-p-phenylenediamine is too high, there is a risk of increasing the dynamic magnification of the vibration-proof rubber, so when 2-mercaptobenzimidazole zinc salt is used in combination (containing 1.8 to 5 parts by mass) as described above, no further improvement in heat resistance can be obtained even if the content of the N,N'-di-2-naphthyl-p-phenylenediamine exceeds 1.1 parts by mass.
[0052] In addition, in anti-vibration rubbers produced using anti-vibration rubber compositions that simply contain an amine-based anti-aging agent in the compounding ratio shown in Patent Document 1, in most cases the dynamic magnification tends to increase, and furthermore, the improvement in heat resistance in long-term heat environments (for example, heat exposure at 100°C for 500 hours or more) is often insufficient.
[0053] As described in Patent Document 3, an antioxidant having a carbonyl group at the α-position is known as a reactive antioxidant and has excellent long-term heat resistance, but is not preferred because the dynamic magnification of an anti-vibration rubber made using an anti-vibration rubber composition containing the antioxidant having a carbonyl group at the α-position is likely to increase. Furthermore, since it often reduces compression set resistance, it is preferable not to contain it in this embodiment.
[0054] It is known that diene rubber has poor ozone resistance. Therefore, when the purpose is to impart ozone resistance, it is preferable to contain, for example, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine and / or N-phenyl-N'-isopropyl-p-phenylenediamine (for example, in a range of 2 parts by mass to 5 parts by mass).
[0055] [Sulfur and sulfur donor compounds (sulfur donors)] The anti-vibration rubber composition of this embodiment contains sulfur as a vulcanizing agent in the range of 0.2 to 0.7 parts by mass (preferably 0.3 to 0.6 parts by mass) and also contains a specific amount of a specific sulfur donor compound.
[0056] Here, it is known that some vulcanization accelerators have both a vulcanization accelerator effect and a sulfur donor (crosslinking agent) effect for low-sulfur (low sulfur content) rubber compositions, and some of these are classified as vulcanization accelerators, but in the explanation of this embodiment, they may be referred to as sulfur donor compounds.
[0057] Generally, as a technique for improving the heat resistance of rubber compositions, a method of crosslinking (vulcanizing) rubber compositions using sulfur donor compounds such as tetramethylthiuram disulfide (TMTD) without containing sulfur (sulfur-free vulcanization method) is known, but the present inventors have conducted detailed studies and found that rubber compositions obtained using the sulfur-free vulcanization method often do not maintain sufficient heat resistance in terms of long-term heat resistance. The reason for this is probably that rubber compositions vulcanized using the sulfur-free vulcanization method contain a large amount of unreacted components and reaction residues derived from the sulfur donor compound, which reduces long-term heat resistance, even if the crosslinked rubber composition reaches a heat-resistant crosslinked form.
[0058] On the other hand, by containing a small amount of sulfur (0.2 to 0.7 parts by mass) as in the vibration-proof rubber composition of this embodiment, it is possible to reduce reaction residues and unreacted residues derived from the sulfur donor compound, which is believed to improve long-term heat resistance.
[0059] The sulfur used in the present embodiment is not particularly limited, but may be, for example, a known compounding material for rubber. Specific examples include powdered sulfur, precipitated sulfur, surface-treated sulfur obtained by surface-treating powdered sulfur or precipitated sulfur, insoluble sulfur, etc.
[0060] As the sulfur donor compound, tetrakis(2-ethylhexyl)thiuram disulfide, tetrabenzyl thiuram disulfide, 2-(4'-morpholinodithio)benzothiazole, 4,4'-dithiodimorpholine, tetramethyl thiuram disulfide, tetraethyl thiuram disulfide, tetrabutyl thiuram disulfide, dipentamethylene thiuram tetrasulfide, etc. can be used. Among these, tetrakis(2-ethylhexyl)thiuram disulfide, tetrabenzyl thiuram disulfide, and 2-(4'-morpholinodithio)benzothiazole are preferably used. In particular, from the viewpoints of heat resistance, compression set resistance, and heat resistant adhesiveness, tetrakis(2-ethylhexyl)thiuram disulfide is more preferably used. The content of tetrakis(2-ethylhexyl)thiuram disulfide can be set within the range of 2 to 7 parts by mass.
[0061] When tetrakis(2-ethylhexyl)thiuram disulfide is used, it tends to have superior long-term heat resistance compared to when other thiuram sulfur donor compounds are used. The reason for this is probably that the reactivity of unreacted components and reaction residues derived from the sulfur donor compound is kept low, so even if the vibration-proof rubber composition is exposed to a hot environment for a long period of time, unnecessary reactions are unlikely to occur.
[0062] Here, the mechanism of general rubber thermal deterioration is often explained by autoxidation (deterioration due to high-temperature autoxidation) that occurs in the presence of oxygen in the air. Even in the case of anti-vibration rubber, it is extremely important to suppress the deterioration of the rubber in the areas exposed on the surface (hereinafter simply referred to as exposed areas).
[0063] However, in the case of anti-vibration rubber that has a portion covered with metal such as a rubber bush (hereinafter simply referred to as a non-exposed portion) or a thick portion (for example, a portion with a rubber thickness of 4 mm or more), changes in the characteristics of the rubber in the non-exposed portion or the rubber inside the thick portion will affect the vibration characteristics even if they are not exposed to air. For this reason, in the case of general anti-vibration rubber, there is a risk that the rubber in the exposed portion is prone to oxidation degradation and surface hardening due to long-term heat aging.
[0064] Therefore, in the anti-vibration rubber of this embodiment, when the purpose is to further reduce the change in vibration characteristics due to long-term heat exposure, 2-(4'-morpholinodithio)benzothiazole is used as the sulfur donor compound. In this way, with an anti-vibration rubber composition using 2-(4'-morpholinodithio)benzothiazole as the sulfur donor compound, the change in hardness of the rubber in the internal part of the anti-vibration rubber is small, and the change in vibration characteristics is suppressed due to the balance between the degree of hardening of the rubber surface in exposed and unexposed parts and the small change in hardness of the rubber in the internal part (for example, the inside of the thick part).
[0065] In the vibration-proof rubber composition of the present embodiment, the content of 2-(4-morpholinodithio)benzothiazole is within the range of 1 to 3 parts by mass, preferably 1.2 to 3 parts by mass. If the content of 2-(4-morpholinodithio)benzothiazole exceeds 3 parts by mass, it is not preferable because the heat-resistant adhesiveness may decrease.
[0066] Also, m-phenylenedimaleimide can be used as a vulcanizing agent in combination with sulfur and a sulfur donor compound.
[0067] [Vulcanization accelerator] In addition, it is preferable to appropriately use a known vulcanization accelerator used as a compounding material for sulfur vulcanized rubber in the vibration-proof rubber composition of this embodiment. The vulcanization accelerator is not particularly limited, and specific examples include sulfenamide compounds such as N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, and N,N-diisopropyl-2-benzothiazole sulfenamide, thiazole compounds such as 2-mercaptobenzothiazole, 2,2'-dibenzothiazolyl disulfide, zinc salt of 2-mercaptobenzothiazole, and cyclohexylamine salt of 2-mercaptobenzothiazole, guanidine compounds such as diphenylguanidine, triphenylguanidine, diorthonitrile guanidine, orthonitrile biguanide, and diphenylguanidine phthalate, and thiuram compounds such as tetramethylthiuram monosulfide.
[0068] Furthermore, for the purpose of adjusting the vulcanization rate and delaying the scorch time, scorch inhibitors such as N-cyclohexylthiophthalimide and N-phenyl-N-(trichloromethylthio)benzenesulfonamide can be preferably used.
[0069] [Carbon black] The anti-vibration rubber composition of the present embodiment can use carbon black appropriately, and examples thereof include known carbon blacks, but are not limited thereto. Specific examples include FT-class, SRF-class, GPF-class, FEF-class, MAF-class, HAF-class, ISAF-class, SAF-class, and other carbon blacks. Among these, FEF-class, MAF-class, and HAF-class carbon blacks are preferably used because of their good balance of rubber strength, durability, and low dynamic magnification. In addition, from the viewpoint of, for example, the support performance for automobile vehicles and low dynamic magnification, SRF-HS-class carbon black, which has a developed structure in the SRF-class, is preferably used.
[0070] [Filler] The anti-vibration rubber composition of the present embodiment may contain a filler for the purpose of adjusting hardness and improving processability. For example, fillers used in ordinary rubber compositions, such as silica (wet silica, dry silica, colloidal silica, etc.), calcium carbonate, clay, talc, etc., may be used as appropriate. These fillers may be used alone or in combination of two or more.
[0071] [Process oil] The anti-vibration rubber composition of this embodiment may contain a process oil for the purpose of adjusting hardness and improving processability. Examples of the process oil include naphthenic oil, paraffinic oil, and aromatic oil. These process oils may be used alone or in combination of two or more. The content of the process oil can be appropriately set, but is preferably within the range of, for example, 0 to 20 parts by mass. If the content of the process oil exceeds 20 parts by mass, there is a risk of a decrease in long-term heat resistance, which is not preferable.
[0072] [Vulcanization aid] The anti-vibration rubber composition of this embodiment preferably contains an appropriate amount of a vulcanization aid such as zinc oxide (ZnO) or zinc oxide complex, and further preferably contains an appropriate amount of other vulcanization aids (e.g., stearic acid, zinc stearate, etc.).
[0073] Here, composite zinc oxide is known to have a layer of zinc oxide (zinc oxide) on the surface and contain an inorganic metal salt inside as a core component, and one example is the META-Z L series (META-Z L40, L50, L60) manufactured by Inoue Lime Industry Co., Ltd.
[0074] The content of zinc oxide or composite zinc white can be appropriately set, but is preferably, for example, 3 parts by mass or more and 15 parts by mass or less per 100 parts by mass of the rubber component.
[0075] The content of stearic acid or zinc stearate can be appropriately set, but is preferably 0.1 to 2 parts by mass, for example, per 100 parts by mass of the rubber component.
[0076] [Processing aids] The anti-vibration rubber composition of the present embodiment may contain a processing aid for the purpose of improving processability. Compounds used in normal rubber processing may be used as the processing aid. Examples of such additives include various additives such as lubricants, tackifiers, dispersants, compatibilizers, and homogenizers.
[0077] [Method for preparing anti-vibration rubber composition] The anti-vibration rubber composition of the present embodiment can be prepared by kneading the above-described essential components, that is, the rubber component, the antioxidant component, and the vulcanizing agent component (and the other materials listed above, if necessary), using a kneading machine such as a pressure kneader, a Banbury mixer, an intermix mixer, or an open roll.
[0078] The anti-vibration rubber of this embodiment is obtained by vulcanizing the above-mentioned anti-vibration rubber composition, and the anti-vibration rubber composition becomes an elastomer for anti-vibration rubber by appropriately vulcanizing it (for example, at a vulcanization temperature of 145 to 170°C for 3 to 30 minutes).
[0079] That is, the anti-vibration rubber made of the elastic body obtained by vulcanizing the anti-vibration rubber composition of this embodiment has excellent long-term heat resistance, a small compression set rate, and a low dynamic magnification ratio, and therefore has excellent vibration insulation properties. Therefore, it can be suitably used as an anti-vibration rubber that is required to withstand severe thermal environments and to isolate vibrations from vibration sources in vehicles such as automobiles and various machines. EXAMPLES
[0080] Examples of this embodiment (Examples 1 to 13) are shown below, but the present invention is not limited to these examples.
[0081] <Preparation of anti-vibration rubber composition> The anti-vibration rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 were prepared by blending and kneading various materials in the ratios shown in Tables 1 to 4. The kneading was carried out by first kneading materials other than the vulcanizing agent, sulfur donor compound, and vulcanization accelerator for 5 minutes using a Banbury mixer to obtain a kneaded product. Next, the kneaded product was cooled using an open roll (cooling water temperature in the open roll was set to about 20°C), while the vulcanizing agent, sulfur donor compound, and vulcanization accelerator were added, and kneaded for 5 minutes to prepare each anti-vibration rubber composition.
[0082] [Table 1]
[0083] [Table 2]
[0084] [Table 3]
[0085] [Table 4]
[0086] The various materials listed in Tables 1 to 4 are as follows. Natural rubber: SVR CV60 Butadiene rubber-1: cis 1,4-bond content 96%, Mooney viscosity at 100℃ (ML 1+4 )63, ARLANXEO Co., Ltd. "BUNA-CB21" Butadiene rubber-2: cis 1,4-bond content 96%, Mooney viscosity at 100℃ (ML 1+4 ) 44. "BR-01" manufactured by ENEOS Material Co., Ltd. Butadiene rubber-3: cis 1,4-bond content 35%, Mooney viscosity at 100℃ (ML 1+4)59, Zeon Corporation "BR1250H" Anti-aging agent-1: N,N'-di-2-naphthyl-p-phenylenediamine, "Nocrac White" manufactured by Ouchi Koh Co., Ltd. · Anti-aging agent - 2:2-mercaptobenzimidazole zinc salt, "Nocrac MBZ" manufactured by Ouchi Koh Co., Ltd. Anti-aging agent-3: (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine), "Nocrac 6C" manufactured by Ouchi Kogyo Co., Ltd. · Anti-aging agent - 4:2-mercaptobenzimidazole, "Nocrac MB" manufactured by Ouchi Koh Co., Ltd. · Anti-aging agent - 5: 2-mercaptomethylbenzimidazole, "Nocrac MMB" manufactured by Ouchi Koh Co., Ltd. Anti-aging agent-6: N-phenyl-N'-(3-methacryloyloxy-2-hydroxypropyl)-p-phenylenediamine, "Nocrac G-1" manufactured by Ouchi Shinko Co., Ltd. Vulcanizing agent: Sulfur, Tsurumi Chemical Industry Co., Ltd. "Kinkajirushi Fine Sulfur 200MESH" Sulfur donor compound-1: Tetrakis(2-ethylhexyl)thiuram disulfide, "Noccela TOT-N" manufactured by Ouchi Koh Co., Ltd. Sulfur donor compound-2: 2-(4-morpholinodithio)benzothiazole, "Noccela MDB-P" manufactured by Ouchi Koh Co., Ltd. Sulfur donor compound-3: Tetramethylthiuram disulfide, "Noccela TT-P" manufactured by Ouchi Koh Co., Ltd. Sulfur donor compound-4: 4,4'-dithiodimorpholine, "Balnoc R" manufactured by Ouchi Koh Co., Ltd. Vulcanization accelerator-1: (N-cyclohexyl-2-benzothiazolyl sulfenamide), "Noccela CZ-G" manufactured by Ouchi Kogyo Chemical Co., Ltd. Vulcanization accelerator - 2:1,3-diphenylguanidine, "Noccela DP" manufactured by Ouchi Kogyo Chemical Co., Ltd. Carbon black-1: Nitrogen adsorption specific surface area 47m 2 / g (MAF grade), "Niteron #10" manufactured by Nippon Steel Carbon Co., Ltd. Carbon black-2: Nitrogen adsorption specific surface area 22m 2 / g (SRF-HS grade), Asahi Carbon Co., Ltd. "Asahi #52" Paraffin wax: (wax) Nippon Seiro Co., Ltd. "Ozoace 0100" Composite zinc oxide: "META-Z-L60" manufactured by Inoue Lime Industry Co., Ltd. Stearic acid: "Camellia stearate" manufactured by Nippon Oil & Fats Co., Ltd. Naphthenic oil: "Crisef Oil H56" manufactured by ENEOS Corporation.
[0087] <Creating evaluation samples (vulcanized rubber)> [Preparation of vulcanized rubber sheets for measuring tensile properties and properties after heat aging] For each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4, vulcanization molding was performed by compression molding using a 2 mm sheet mold with a cavity having a thickness of approximately 2 mm at 160°C for a vulcanization time of 10 minutes to obtain a vulcanized rubber sheet having a thickness of 2 mm (hereinafter simply referred to as the evaluation rubber sheet).
[0088] [Preparation of vulcanized rubber test pieces for compression set testing] Each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4 was compression molded using a cylindrical test piece preparation mold having a diameter of 29.0 mm and a height of 12.5 mm to undergo vulcanization molding at 160°C for a vulcanization time of 15 minutes, to obtain cylindrical vulcanized rubber test pieces (hereinafter simply referred to as rubber test pieces) having a diameter of 29.0 mm and a height of 12.5 mm for type A durometer hardness and compression set tests.
[0089] [Preparation of anti-vibration rubber test pieces] In preparing the vibration-proof rubber test piece 1 shown in FIG. 1, first, two 50 mm x 50 mm iron metal fittings 2 with a bolt 3 standing at the center of one side were prepared, and the surface of each metal fitting 2 on which the bolt 3 was not standing was roughened by shot blasting. Next, Chemlock 205 (manufactured by Lord Far East Co., Ltd.) was applied as an undercoat adhesive to each of the surfaces of each metal fitting 2 on which the bolt 3 was not standing, and dried in an atmosphere at 80°C for 20 minutes to form an undercoat adhesive layer (thickness 10 μm). After each metal fitting 2 on which this undercoat adhesive layer was formed was cooled to room temperature, Chemlock 6125 (manufactured by Lord Far East Co., Ltd.) was applied as an overcoat adhesive to the surface of the undercoat adhesive layer, and dried in an atmosphere at 80°C for 20 minutes to form an overcoat adhesive layer (thickness 10 μm). Then, each metal fitting 2 was placed in the molding die (so that the topcoat adhesive layer of each metal fitting 2 was facing each other), and then, using an injection molding machine, unvulcanized rubber (anti-vibration rubber composition) was filled between each metal fitting 2 in the molding die, and vulcanized (160°C x 15 minutes) to produce a square anti-vibration rubber test piece 1 with metal fitting 2 formed into a rectangular prism of 40 mm x 40 mm x 30 mm as shown in Figure 1.
[0090] <Testing method, evaluation method and judgment of anti-vibration rubber composition (vulcanized rubber)> The test methods and evaluation methods for the anti-vibration rubber compositions (vulcanized rubber) of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4 are as follows. The evaluation results and judgment results are also shown in Tables 5 to 8 below.
[0091] [Initial physical properties: Type A durometer hardness] Four evaluation rubber sheets were prepared from each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4, and laminated to obtain laminated sheets (i.e., laminated sheets with a four-layer structure and a thickness of about 8 mm).The hardness (HA) of each laminated sheet was measured using a type A durometer in accordance with JIS K6253-3 (2012).
[0092] [Initial physical properties: tensile properties] For each of the evaluation rubber sheets obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4, a JIS No. 3 dumbbell was used to punch out the rubber sheets, and the elongation at break (EB) and tensile strength at break (TB) were measured in accordance with JIS K 6251.
[0093] [Compression set rate] Each rubber test piece obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 shown in Tables 1 to 4 was compressed by 25.0% in the height direction (height 9.38 mm) using a jig in accordance with JIS K6262 (2013), and left in a gear-type aging tester (forced circulation type heat aging tester) at an atmospheric temperature of 100°C for 22 hours, and then the rubber test piece was removed together with the jig and quickly released. After this release, the rubber test piece was left on a wooden stand in an atmosphere of 23°C for 30 minutes, and the height (h1) of the rubber test piece was measured, and the compression set CS (%) was calculated.
[0094] The calculation method (formula) for compression set CS complies with JIS K6262 (2013) and is as shown in the following formula (1).
[0095] CS(%)=((h0-h1) / (h0-hs))×100 ……(1) In this formula (1), h0 is the thickness (mm) of the rubber test piece before compression, h1 is the thickness (mm) of the rubber test piece after it has been removed from the compression device, and hs is the thickness (mm) of the spacer used.
[0096] The smaller the value of the compression set CS calculated by formula (1), the smaller the compression set rate and the better the heat setting resistance. Therefore, in order to evaluate the product, the compression set CS (%) was judged as "◎" when it was less than 30%, "◯" when it was 30% or more and less than 35%, and "×" when it was 35% or more.
[0097] [Heat aging resistance-1] For each of the evaluation rubber sheets obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 listed in Tables 1 to 4, first, a JIS No. 3 dumbbell was used to punch out the rubber sheets, and then a heat aging test was performed in accordance with JIS K 6257 by holding the sheets in a gear-type aging tester (forced circulation type heat aging tester) at an ambient temperature of 100°C for various holding times (72 hours, 168 hours, 240 hours, 336 hours, 500 hours, 1000 hours, 1500 hours).
[0098] Next, the hardness (HA), elongation at break (EB), and tensile strength at break (TB) after the heat aging test were measured in the same manner as in the above item [Initial physical properties].
[0099] The AHA (Duro-A) was calculated from the difference in hardness (HA) before and after the heat aging test. The change rates (the rate of change of the value after the heat aging test from the value before the aging test) AcEB (%) and AcTB (%) were calculated from the elongation at break (EB) and tensile strength at break (TB) before and after the heat aging test.
[0100] In addition, as for the evaluation, when both AcEB(%) and AcTB(%) are 50% or less after 1000 hours of heat aging test (heat aging time), it was judged as "Good", and when AcEB(%) is 60% or less after 1500 hours of the heat aging test, it was judged as "Good". Even if both or either of AcEB(%) and AcTB(%) are more than 50% after 1000 hours of the heat aging test, when both AcEB(%) and AcTB(%) are 60% or less, it was judged as "Good", since it may be usable as heat resistant rubber. Furthermore, when AcEB(%) is more than 60% after 1000 hours of the heat aging test, it was judged as "Poor".
[0101] [Initial vibration characteristics: static characteristics Ks, dynamic characteristics Kd100, dynamic magnification] For each test piece 1 obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15, first, in accordance with JISK 6385 (2012), an axial load was applied via each bolt 3 to compress the test piece 1 in the axial direction (bolt 3 axial direction) by 5 mm (compressed at a displacement rate of 10 mm / min), and then the test piece 1 was once deloaded (deloaded at a displacement rate of 10 mm / min). This compression-deloading process was repeated twice. After this, the test piece 1 was compressed again by 5 mm (i.e., the third loading process), and the load-deflection characteristics at the time of compression (the third loading process) were measured, and a load-deflection curve was created based on the results. Then, the load values P1 and P2 (unit: N) when the deflection became 2 mm and 4 mm were read from the load-deflection curve, and the load values P1 and P2 were appropriately substituted into the relational expression "Ks=(P2-P1) / 2" to calculate the static spring constant Ks (N / mm).
[0102] Separately, each test piece 1 was compressed 3 mm in the axial direction via each bolt 3 in the same manner as above, and a test was performed in which a constant displacement harmonic compression vibration of amplitude ±0.05 mm was applied at a frequency of 100 Hz from one bolt 3 side (for example, the lower side in the figure) of the test piece 1 in the compressed state, centered on the position where the test piece 1 was compressed 3 mm, and the dynamic spring constant Kd100 (N / mm) at 100 Hz was calculated in accordance with the "non-resonance method (a)" in the "Test method for vibration-proof rubber" of JIS-K-6385-2012. Then, the dynamic magnification (=Kd100 / Ks) was calculated from the calculated dynamic spring constant (Kd100) and the calculated static spring constant (Ks).
[0103] As mentioned above, the dynamic magnification ratio is a value that varies greatly depending on the type and content of the polymer and carbon black used. The smaller the dynamic magnification ratio, the better, but a balance with reinforcement and other factors is necessary. In the evaluation, the dynamic magnification ratio (1.56) when the anti-vibration rubber composition of Example 1 is used is defined as the judgment standard value, and a dynamic magnification ratio of +8% or less than the judgment standard value (i.e., 1.68 or less) is judged as "Good", and a dynamic magnification ratio of more than +8% than the judgment standard value (i.e., more than 1.68) is judged as "Poor".
[0104] [Heat aging resistance-2] For each test piece 1 obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15, a heat aging test was first performed by holding the test piece in a gear-type aging tester (forced circulation type heat aging tester) at an ambient temperature of 100°C for various holding times (72 hours, 168 hours, 240 hours, 336 hours, 500 hours, 1000 hours, 1500 hours).
[0105] Next, after the heat aging test (after removing the test piece 1 from the gear-type aging tester), the test piece 1 was left at an ambient temperature of 23°C for 16 hours or more and 3 days or less, and then the static spring constant (Ks) was measured in the same manner as in the above item [Initial vibration characteristics].
[0106] The rate of change AcKs (%) (the rate of change of the value after the heat aging test relative to the value before the heat aging test) was calculated from the difference between the static spring constant (Ks) before and after the heat aging test.
[0107] In addition, as an evaluation, a case where AcKs (%) was +25 or less for all of the holding times (heat aging times) in the heat aging test from 72 hours to 1500 hours was judged as "◎". In addition, a case where AcKs (%) was +30 or less at the holding time of 1000 hours and AcKs (%) was +40 or less at the holding time of 1500 hours was judged as "◯". In addition, a case where AcKs (%) was more than +30 at the holding time of 1000 hours and / or AcKs (%) was more than +40 at the holding time of 1500 hours was judged as "×".
[0108] [Heat resistance adhesion test-1, 2] In heat-resistant adhesion test-1, each test piece 1 obtained using each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15 was first elongated 50% (elongated in the vertical direction in FIG. 1) via each bolt 3 in the same manner as above, and held for 60 minutes in a gear-type aging tester (forced circulation type heat aging tester) at an atmospheric temperature of 100°C, and the presence or absence of peeling of the adhesive of each metal fitting 2 was visually observed. Thereafter, each test piece was held for 30 minutes in atmospheres each heated by 10°C each, and the visual confirmation of the presence or absence of peeling of the adhesive of each metal fitting 2 in each atmosphere was repeated, and finally, each test piece was held for 30 minutes in a 200°C atmosphere, and the presence or absence of peeling of the adhesive of each metal fitting 2 was confirmed, and the test was completed.
[0109] In this heat-resistant adhesion test-1, it was determined that the higher the temperature at which peeling of each metal fitting 2 could be prevented, the better the heat-resistant adhesion. Tables 5 to 8 list the highest temperatures at which peeling could be prevented. For example, if there was no peeling at 160°C, but peeling occurred at 170°C, this was recorded as "160°C" in Tables 5 to 8. If peeling could be prevented even at 200°C, this was recorded as "200°C OK."
[0110] In addition, in this heat-resistant adhesion test-1, two test pieces 1 were prepared for each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15, and the test results of the two test pieces 1 that showed the lower peeling temperature were used as an index of heat-resistant adhesion in the heat-resistant adhesion test-1.
[0111] Next, in heat-resistant adhesion test-2, the same test pieces 1 as in heat-resistant adhesion test-1 were first stretched 40% (stretched in the vertical direction in Figure 1) via each bolt 3 as described above, and then held in a gear-type aging tester (forced circulation type heat aging tester) at an ambient temperature of 100°C for various holding times (24 hours, 48 hours, 72 hours), and the presence or absence of adhesive peeling of each metal fitting 2 was visually observed after each holding time had elapsed.
[0112] Then, for the test pieces 1 in which no peeling was observed even when the holding time was set to 72 hours (after 72 hours had elapsed), the test pieces 1 were subsequently held in the testing machine at an ambient temperature of 100°C for several days (held in the testing machine for 30 days from when they were first placed in the testing machine), and then the presence or absence of peeling of the adhesive of each metal fitting 2 was visually observed.
[0113] In this heat-resistant adhesion test-2, two test pieces 1 were prepared for each of the vibration-proof rubber compositions of Examples 1 to 13 and Comparative Examples 1 to 15, and the test result of the two test pieces 1 that showed the earliest peeling was used as an index of heat-resistant adhesion in the heat-resistant adhesion test-2. In Tables 5 to 8, the cases in which there was no peeling of the metal fittings 2 even after being held in the test machine for 30 days are recorded as "30 days ◯".
[0114] In addition, the evaluation was judged as "◎" when the heat resistance limit temperature (the highest temperature at which peeling could be prevented) in heat resistance adhesion test-1 was 170°C or higher and the result of "30 days ◯" was obtained in heat resistance adhesion test-2. In addition, even if the heat resistance limit temperature in heat resistance adhesion test-1 was less than 170°C, the result of "30 days ◯" was obtained in heat resistance adhesion test-2. In addition, the result of "30 days ◯" was not obtained in heat resistance adhesion test-2 (when peeling occurred before 30 days had passed in the testing machine) and it was judged as "X".
[0115] [Overall Judgment] If there is even one "X" result in each of the evaluation judgments shown above, the overall judgment is judged as "X." Also, if there is no "X" result in each evaluation judgment and there is one or less "△" result (other items are "O" or "◎"), the overall judgment is judged as "O."
[0116] [Table 5]
[0117] [Table 6]
[0118] [Table 7]
[0119] [Table 8]
[0120] <<Verification Results by Comparison of Examples 1 to 13 and Comparative Examples 1 to 15>> From the mixing ratios of various materials shown in Tables 1 to 4 and the results shown in Tables 5 to 8, the following can be seen.
[0121] First, in each of the vibration-proof rubber compositions of Examples 1 to 8, natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) are used as the main rubber components, and when the total rubber components are taken as 100 parts by mass, the composition contains 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur as a vulcanizing agent, and 2 to 7 parts by mass of tetrakis(2-ethylhexyl)thiuram disulfide as a sulfur donor compound (hereinafter simply referred to as the category composition of Examples 1 to 8).
[0122] And, according to the configurations of Examples 1 to 8, it is found that extremely excellent results are obtained in compression set rate (heat setting resistance), heat resistance (in item [heat aging resistance-1], the deterioration of material properties due to long-term heat aging is small), initial vibration characteristics (low dynamic magnification), and heat-resistant adhesion. Also, the change in vibration characteristics (change in vibration-proof characteristics due to long-term heat aging in test piece 1 (thick anti-vibration rubber) in item [heat aging resistance-2]) is small, and it is found that an extremely excellent heat-resistant anti-vibration rubber composition and heat-resistant anti-vibration rubber are obtained.
[0123] On the other hand, in the anti-vibration rubber compositions of Comparative Examples 1 to 8, at least one of the types and contents of the antioxidant, sulfur, and sulfur donor compound is different from the category configurations of Examples 1 to 8, and it is found that at least one of the evaluation judgments shown in Table 7 is judged to be "X."
[0124] Next, in each of the vibration-proof rubber compositions of Examples 9 to 13, natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) are the main rubber components, and when the total rubber components are taken as 100 parts by mass, they contain 2-mercaptobenzimidazole zinc salt in the range of 1.8 to 5 parts by mass, N,N'-di-2-naphthyl-p-phenylenediamine in the range of 0.2 to 1.1 parts by mass, sulfur as a vulcanizing agent in the range of 0.2 to 0.7 parts by mass, and 2-(4-morpholinodithio)benzothiazole as a sulfur donor compound in the range of 1.2 to 3 parts by mass (hereinafter simply referred to as the Examples 9 to 13 category configuration).
[0125] And, according to the configurations of Examples 9 to 13, it is found that the change in vibration characteristics (change in vibration-proof characteristics due to long-term heat aging in test piece 1 (thick anti-vibration rubber) in item [heat aging resistance-2]) is extremely small, and more excellent results are obtained. Also, in the compression set rate (heat set resistance) and heat resistance (item [heat aging resistance-1], the deterioration of physical properties is small until the holding time reaches 1000 hours at an atmospheric temperature of 100°C, and it is found that excellent heat resistance is obtained. Regarding heat-resistant adhesion, although the adhesion in a hot atmosphere significantly exceeding 100°C may be insufficient, sufficient adhesion is obtained even when tensile stress is applied for 30 days in a hot atmosphere of 100°C, and it is found that it can be used sufficiently as a heat-resistant anti-vibration rubber composition. Also, it is found that the compression set rate (heat set resistance) and initial vibration characteristics (low dynamic magnification) also have sufficiently good results.
[0126] On the other hand, in the anti-vibration rubber compositions of Comparative Examples 9 to 15, at least one of the types or contents of the antioxidant, sulfur, and sulfur donor compound is different from the category configurations of Examples 9 to 13, and it is found that at least one of the evaluation judgments shown in Table 8 is judged to be "X."
[0127] The vibration-proof rubber compositions of Comparative Examples 12 and 15 contained a large amount of 2-(4-morpholinodithio)benzothiazole or 4,4'-dithiodimorpholine as a sulfur donor compound. However, in the test pieces 1 prepared in each case, peeling occurred easily between the metal fittings 2 and the rubber part with the force of the fingers. Therefore, it was determined that these were unsuitable as vibration-proof rubber with metal fittings, and testing using these test pieces 1 was discontinued.
[0128] Focusing on the butadiene rubber used in the vibration-proof rubber compositions of Examples 1 to 13, the Mooney viscosity (ML 1+4 It was confirmed that by setting the value of the modulus of elasticity (b) within the range of 50 to 75, the vibration-proofing characteristics (low dynamic magnification) and rubber strength were improved, and more preferable results were obtained.
[0129] From the above results, it can be said that the anti-vibration rubber compositions of Examples 1 to 8 show little deterioration in material properties even under extremely long-term heat environments (for example, an extremely long period of 1,500 hours at 100°C), and also have excellent heat resistance, vibration characteristics, and heat-resistant adhesion, making them extremely excellent anti-vibration rubber compositions.
[0130] Furthermore, the anti-vibration rubber compositions of the scope of Examples 9 to 13 show little change in the vibration characteristics of the anti-vibration rubber even under extremely long-term heat environments (for example, an extremely long period of 1500 hours at 100°C), and also show little deterioration in the material properties even under long-term heat environments (for example, a long period of 1000 hours at 100°C), and are excellent in heat resistance to settling and vibration characteristics.In terms of heat-resistant adhesion, no peeling occurs even when tensile stress is continuously applied under an extremely long-term heat environment (for example, 30 days at 100°C), so they can be said to be excellent anti-vibration rubber compositions. [Explanation of symbols]
[0131] 1...Test piece 2...Metal fittings 3...Bolt (support rod)
Claims
1. A vibration-proof rubber composition containing natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) as main rubber components, A vibration-proof rubber composition containing 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur, and 2 to 7 parts by mass of tetrakis(2-ethylhexyl)thiuram disulfide, based on 100 parts by mass of the total rubber component.
2. A vibration-proof rubber composition containing natural rubber (NR) and / or isoprene rubber (IR) and butadiene rubber (BR) as main rubber components, A vibration-proof rubber composition containing 1.8 to 5 parts by mass of 2-mercaptobenzimidazole zinc salt, 0.2 to 1.1 parts by mass of N,N'-di-2-naphthyl-p-phenylenediamine, 0.2 to 0.7 parts by mass of sulfur, and 1.2 to 3 parts by mass of 2-(4-morpholinodithio)benzothiazole, based on 100 parts by mass of the total rubber component.
3. The main rubber component is a blend of natural rubber (NR) and butadiene rubber (BR) in an NR / BR ratio of 90 / 10 to 60 / 40, The butadiene rubber has a Mooney viscosity at 100° C. (ML 1+4 3. The anti-vibration rubber composition according to claim 1, wherein the molecular weight of the polymer is 50 to 75.
4. 3. A vibration-proof rubber comprising the vibration-proof rubber composition according to claim 1 or 2, vulcanized and bonded to the surface of a metal fitting via an adhesive layer on the surface of the metal fitting, so that the metal fitting and vulcanized rubber made from the vibration-proof rubber composition are integrally formed.
5. 4. A vibration-proof rubber comprising: a metal fitting having a surface on which the vibration-proof rubber composition according to claim 3 is vulcanized and bonded via an adhesive layer on the metal fitting surface, and the metal fitting and a vulcanized rubber made of the vibration-proof rubber composition are integrally formed.
Citation Information
Patent Citations
Rubber composition and rubber cushion or automobile
JP2002194140A
Rubber composition for vibration-proof rubber
JP2015004005A
Run flat tire
JP2016035011A
Vibration-proof rubber composition and vibration-proof rubber
JP2023106743A
Run flat tire
US20160031268A1